Seismic response of buried pipelines: a state-of-the-art review - Datta, T.K (Nuclear engineering and design, 1999)
A state-of-the-art review of the seismic response of buried pipelines is presented. The review includes modeling of soil–pipe system and seismic excitation, methods of response analysis of buried pipelines, seismic behavior of buried pipelines under different parametric variations, seismic stresses at the bends and intersections of network of pipelines. pipe damage in earthquakes and seismic risk analysis of buried pipelines. Based on the review, the future scope of work on the subject is outlined.